Stress-Axis Regulation by Vitamin D3 in Multiple Sclerosis - Rolf, Linda; Damoiseaux, Jan; Huitinga, Inge; Kimenai, Dorien; van den Ouweland, Jody; Hupperts, Raymond; Smolders, Joost (Frontiers in Neurology, 2018)
INTRODUCTION: Multiple sclerosis (MS) has been associated with both a poor vitamin D status and hyperactivity of the hypothalamus-pituitary-adrenal (HPA) axis. Since nuclear receptor ligands may regulate each other, we explored the association of vitamin D3 supplements with circadian cortisol levels in a double-blind and placebo-controlled supplementation study. METHODS: Female patients with relapsing-remitting MS received vitamin D3 supplements (4000 IU/day; n=22) or placebo (n=19) during 16 weeks. Salivary cortisol levels, repeatedly measured during the day, and serum 25(OH)D levels were assessed before (T0) and after (T1) this treatment period. RESULTS: Median 25(OH)D levels at T1 were 139.9 nmol/L (interquartile range 123.5 – 161.2) and 74.5 nmol/L (58.6 – 88.1) in the vitamin D3 and placebo group, respectively (p<0.001). Comparisons within and between groups showed no differences in area under the curve (AUC) and slope of the cortisol day curve. Although the AUC of the cortisol awakening response (CAR, sampling each 15 minutes the first hour after awakening) showed a reduction over time in the vitamin D3 group (39.16 nmol/L (27.41 – 42.07) at T0 to 33.37 nmol/L (26.75 – 38.08) at T1) compared to the placebo group (33.90 nmol/L (25.92 – 44.61) at T0 to 35.00 nmol/L (25.46 – 49.23) at T1; p= 0.044), there was no significant difference in AUC of CAR at T1 corrected for baseline AUC of CAR (P=0.066). CONCLUSION: Suppression of HPA-axis activity by vitamin D3 supplements in non-depressed MS patients may be best reflected by CAR as primary outcome measure. Further studies should address this interaction and its potential implications for the disease course of MS. REGISTRATION: This study was registered on ClinicalTrials.gov (NCT02096133) and EudraCT (2014-000728-97).